A predicted new catalyst to replace noble metal Pd for CO oxidative coupling to DMO. Issue 8 (17th March 2022) - Zhao, Juan; Yin, Li-Fei; Ling, Li-Xia; Zhang, Ri-Guang; Fan, Mao-Hong; Wang, Bao-Jun
Abstract : The reaction mechanisms of CO oxidative coupling to dimethyl oxalate (DMO) on different β-Mo2 C(001) based catalysts have been studied by the density functional theory (DFT) method. Abstract : The reaction mechanisms of CO oxidative coupling to dimethyl oxalate (DMO) on different β-Mo2 C(001) based catalysts have been studied by the density functional theory (DFT) method. The activity and selectivity of DMO formation on Mo termination of β-Mo2 C(001) are poor, and its C termination has no catalytic activity. After loading a Cu monolayer, the CuML /Mo2 C(001)–Mo catalyst shows poor activity for the CO oxidative coupling reaction, but on CuML /Mo2 C(001)–C, the CO oxidative coupling reaction can occur owing to the synergistic effect between the Cu monolayer and Mo2 C(001), and it is expected to be a catalyst to replace precious metal Pd in DMO generation. Furthermore, the d-orbital state density of the Cu monolayer on CuML /Mo2 C(001)–C is most similar to that of the Pd monolayer of Pd(111), which is the reason why CuML /Mo2 C(001)–C has high activity and selectivity to DMO on the CO oxidative coupling reaction.